2010
DOI: 10.1590/s0100-83582010000400009
|View full text |Cite
|
Sign up to set email alerts
|

Resposta de diferentes populações de Digitaria insularis ao herbicida glyphosate

Abstract: RESUMO -Objetivou-se com estse trabalho avaliar o controle químico de diferentes populações de capim-amargoso (Digitaria insularis) pelo herbicida glyphosate por meio de curva de dose-resposta, além de propor tratamentos alternativos para as populações mais tolerantes. O delineamento experimental foi o de blocos ao acaso, com quatro repetições, em esquema fatorial 5 x 9. As sementes de capim-amargoso foram coletadas em cinco locais: área de produção de grãos da Fazenda de Ensino, Pesquisa e Produção da UNESP, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 15 publications
1
13
0
9
Order By: Relevance
“…The loss of IR (%) of this species can be attributed to its lower competitive ability against the weed community in the area. According to Correia et al (2010), sourgrass has slow initial growth until 45 days after emergence, so even presenting high rDe (%) and rFr (%) in the initial stages, this weed was eventually suppressed at the end of the cycle by more dominant species, such as, tropical spiderwort and guinea grass. A dominant plant is characterized by large area of ground cover, great accumulation of mass and great distribution across the area (Concenço et al, 2013a).…”
Section: Resultsmentioning
confidence: 99%
“…The loss of IR (%) of this species can be attributed to its lower competitive ability against the weed community in the area. According to Correia et al (2010), sourgrass has slow initial growth until 45 days after emergence, so even presenting high rDe (%) and rFr (%) in the initial stages, this weed was eventually suppressed at the end of the cycle by more dominant species, such as, tropical spiderwort and guinea grass. A dominant plant is characterized by large area of ground cover, great accumulation of mass and great distribution across the area (Concenço et al, 2013a).…”
Section: Resultsmentioning
confidence: 99%
“…The R/S factor corresponds to the division of LD50, LD80 or LD95 of the unknown susceptibility biotype by the susceptible biotype (Christoffoleti & López-Ovejero, 2008). Correia et al (2010) also reported glyphosate differential susceptibility of sourgrass populations, what enunciated the selection of glyphosate-resistant biotypes. In this work, doses up to 3,988 g ha -1 a.e.…”
Section: Resultsmentioning
confidence: 88%
“…Based on the Scott-Knott test at 5 % probability, means followed by lowercase letters, in the columns, compare the populations within each herbicide/ control treatment, and capital letters, in the rows, compare the herbicide/control treatments within each population. When studying the response of five populations of D. insularis to glyphosate herbicide, Correia et al (2010) reported that the populations of Campo Florido, MG, and Rio Verde, GO, both areas of grain production, were considered susceptible; the ones in Jaboticabal, SP (area of grain production) and Matão, SP (orange orchard), tolerant; and the ones in the non agricultural area were considered as having an intermediate sensitivity. For an effective control (100%) of the plants from Jaboticabal, it was necessary to apply 6.0 kg ha -1 of glyphosate.…”
Section: Resultsmentioning
confidence: 99%